2008
DOI: 10.1295/polymj.pj2007223
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Large Nanomembranes by Radical Polymerization of Multifunctional Acrylate Monomers

Abstract: Nanomembranes and naosheets are among the most interesting nanomaterials.1,2 They are characterized by one nanometer dimension and two micro-to-macroscopic dimensions. This unique dimensional combination produces interesting features that are not attainable with other nanomaterials of different dimensionality such as nanocrystals, 3,4 nanoparticles, [5][6][7] and nanotubes. 8-10The macroscopic robustness is essential for application of such features particularly in case of giant nanomembranes. We have shown re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…We have reported that robust nanomembranes are fabricated from a variety of densely crosslinked materials such an inorganic/organic hybrid, 29 thermosetting resins, 30,31 and photopolymers. 32 Because a nanomembrane layer was formed on a substrate coated with a sacrificial polymer, dissolution of the sacrificial layer detaches the nanomembrane into/onto a solvent (see ESI † for more details). One definitive advantage of the process is the easy transfer of a nanomembrane onto other solid substrates.…”
Section: Introductionmentioning
confidence: 99%
“…We have reported that robust nanomembranes are fabricated from a variety of densely crosslinked materials such an inorganic/organic hybrid, 29 thermosetting resins, 30,31 and photopolymers. 32 Because a nanomembrane layer was formed on a substrate coated with a sacrificial polymer, dissolution of the sacrificial layer detaches the nanomembrane into/onto a solvent (see ESI † for more details). One definitive advantage of the process is the easy transfer of a nanomembrane onto other solid substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The elastic modulus of PEGDA (Mn 575) has a broad reported range of moduli of ≈10 kPa up to ≈100 MPa, depending on photoinitiator concentration in the resist and degree of polymerization of the final polymer . Acrylate‐based polymers such as PETA can have moduli ranging from 0.1 to 4 GPa . It is important to point out that, although linear fits of the force‐displacement curves were used to calculate the structure spring constants, it can be seen from Figure d that the response of PEGDA springs was not linear.…”
Section: Fabrication Parameters For Each Spring Type Tested Along Wimentioning
confidence: 99%
“…17,18 Its importance is supported even in the case of acrylate polymers, and robust nanomembranes were available from pentaerythritol tetraacrylate (PETA) that would lead to higher cross-linking density. 19 Structural rigidity of precursor materials may also contribute to the macroscopic robustness. In the case of acrylic monomers, Kayarad-R280 provides a robust nanomembrane, in spite of its functional group density which is not greater than that of HDODA.…”
Section: Cross-linking Density and Structure Of Precursor Moleculementioning
confidence: 99%
“…This difference appears to arise from the presence of rigid molecular components in Kayarad-R280. 19…”
Section: Cross-linking Density and Structure Of Precursor Moleculementioning
confidence: 99%
See 1 more Smart Citation